Tridoped Reduced Graphene Oxide as a Metal-Free Catalyst for Oxygen Reduction Reaction Demonstrated in Acidic and Alkaline Polymer Electrolyte Fuel Cells - Van Pham, Chuyen; Klingele, Matthias; Britton, Benjamin; Vuyyuru, Koteswara Rao; Unmuessig, Tobias; Holdcroft, Steven; Fischer, Anna; Thiele, Simon (Advanced Sustainable Systems, 2017)
Recently, it has been demonstrated that doping of graphene by elements such as N, S, or F creates active sites for the oxygen reduction reaction (ORR). This results from bond polarization caused by the difference in electronegativity between heteroatom dopants and carbon, and/or the presence of defects within the graphene lattice. In this work, fluorine, nitrogen, and sulfur tridoped reduced graphene oxide (F,N,S-rGO) is designed to combine these catalytically active sites. F,N,S-rGO can be inexpensively synthesized by a facile and scalable route involving pyrolysis at 600 °C of sulfur-doped rGO in the presence of Nafion and dimethyl formamide (DMF). The pyrolysis of Nafion and DMF provides F• and N• radicals which serve as doping agents. Rotating disk electrode investigations reveal the ORR catalytic activities of F,N,S-rGO in both acidic and alkaline media, which are consistent with the real performances of the respective polymer electrolyte fuel cells (PEFCs). Maximum power densities of 14 and 46 mW cm−2 are obtained for the acidic and alkaline PEFCs, respectively, using F,N,S-rGO as ORR catalysts. To the best of knowledge, this is the first report on the synthesis of F,N,S tridoped rGO and on its ORR activity in both acidic and alkaline PEFCs.
CRIS-Team Scopus Importer:2023-03-29
Keywords: fuel cells; metal-free catalysts; oxygen reduction reaction; tridoped graphene